Daya Simpan Gula Siwalan Kristal Ditinjau Dari Jenis Pengemas Dan Kondisi Pengemasan (Jurnal Teknologi Pangan, 2013)
This research aimed to defined a proper packaging and a  way to pack for ‘gula siwalan kristal’ storage-life. This research used random block design which was containing two factors treatment with three (3) times repeating. First factor was the kind of packaging (P1 = Polyethylene, P2 = Polypropylene). Second factor was a way to pack (V1 = packing without vacuum, V2 = with vacuum). It will be analysed every 5 weeks. The parameters would be analysed were water contain and sum micro-organism as parameter, also hedonic test.    The result showed that ‘gula siwalan kristal’ had a lower water contain when  it packed by vacuum.  Polyethylene and vacuum (P1V2) could press the amount of micro-organism. Based on hedonic test showed that a kind of packaging and a way to pack did not effect to the colour of  ‘gula siwalan kristal’ but did to performance of it for 5, 10 and 15 weeks storages.Key words: ‘gula siwalan kristal’, packaging, polyethylene, polypropylene and vacuum